2020
DOI: 10.1038/s41590-020-0706-5
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-6 is the nexus transcription factor of T follicular helper cells via repressor-of-repressor circuits

Abstract: T follicular helper (T FH ) cells are a distinct type of CD4 + T cells that are essential for most antibody and B lymphocyte responses. T FH cell regulation and dysregulation is involved in a range of diseases. Bcl-6 is the lineage defining transcription factor of T FH cells and its activity is essential for T FH cell differentiation and function. However, how Bcl-6 controls T FH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
139
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(165 citation statements)
references
References 61 publications
14
139
0
Order By: Relevance
“…25 As discussed below, this study confirmed previous work highlighting that Bcl6 acts as a hub for the transcriptional repression of pathways that inhibit Tfh differentiation. 25 Importantly, this and other studies have recently demonstrated that Bcl6 repression of these transcriptional networks occurs independently of Blimp-1, further highlighting the indispensable role for Bcl6 in Tfh fate commitment. 25,26 Several unique structural features of the Bcl6 protein allow it to interact with diverse transcription factors and chromatin modifiers to form transcriptional complexes.…”
Section: Bcl6supporting
confidence: 89%
See 4 more Smart Citations
“…25 As discussed below, this study confirmed previous work highlighting that Bcl6 acts as a hub for the transcriptional repression of pathways that inhibit Tfh differentiation. 25 Importantly, this and other studies have recently demonstrated that Bcl6 repression of these transcriptional networks occurs independently of Blimp-1, further highlighting the indispensable role for Bcl6 in Tfh fate commitment. 25,26 Several unique structural features of the Bcl6 protein allow it to interact with diverse transcription factors and chromatin modifiers to form transcriptional complexes.…”
Section: Bcl6supporting
confidence: 89%
“…25 Importantly, this and other studies have recently demonstrated that Bcl6 repression of these transcriptional networks occurs independently of Blimp-1, further highlighting the indispensable role for Bcl6 in Tfh fate commitment. 25,26 Several unique structural features of the Bcl6 protein allow it to interact with diverse transcription factors and chromatin modifiers to form transcriptional complexes. These interactions permit Bcl6 to control gene expression in CD4 + T-cell precursors and in mature Tfh cells.…”
Section: Bcl6mentioning
confidence: 53%
See 3 more Smart Citations